MUSLIM RELIGIOUS EDUCATION SYSTEM IN INDONESIA - Turdiyeva Dilafruz Makhmudjanovna (Western European Studies, 2024)
The educational system is important in every state and period. It is important to study the experience of states, to introduce them in some places. In particular, the article also explores the Islamic religious education system in Indonesia, where the Southeast Asian region is considered a Muslim country.
Keywords: Indonesia; religious education; Islam; Minister of Education